Regulatory histories of recently withdrawn ovarian cancer treatment indications of 3 PARP inhibitors in the US and Europe: lessons for the accelerated approval pathway - Mahnum Shahzad; Huseyin Naci; Katharine M. Esselen; Joseph A. Dottino; Anita K. Wagner (Taylor & Francis Group, 2024)
Background Withdrawals of drug indications may reveal potential inadequacies in the regulatory approval processes of new drugs. Understanding potential weaknesses of the regulatory approval process is paramount given the increasing use of expedited pathways. In this paper, we focus on three poly-ADP-ribose polymerase inhibitors (olaparib, rucaparib and niraparib) for the treatment of women with heavily pretreated, recurrent ovarian cancer, which were eventually withdrawn.Methods We use a comparative case study approach to evaluate the regulatory histories of these drug indications in the US and Europe.Results Two drug indications benefited from the FDA's accelerated approval pathway, which explicitly lowers the bar for evidence of efficacy at the time of approval. Following accelerated approval, manufacturers are mandated to conduct post-marketing studies to confirm clinical benefit. The FDA granted accelerated approval to olaparib and rucaparib based on data on surrogate endpoints and converted the approval to regular approval after the submission of additional data on surrogate endpoints from one of two required confirmatory trials, that is, without data on clinical benefit. Niraparib directly received regular approval based only on data on a surrogate endpoint. By contrast, the EMA granted conditional marketing authorisation to rucaparib and was quicker to restrict usage than the FDA.Conclusion The regulatory histories of these drug indications highlight the need to reform the accelerated approval pathway by ensuring that post-marketing requirements are followed, and that regular approval is only based on evidence of clinical benefit.